1965
DOI: 10.1055/s-0038-1654849
|View full text |Cite
|
Sign up to set email alerts
|

Activated Human Hageman Factor (XII)*

Abstract: SummaryAn improved method for the isolation of highly purified active human Hageman factor has been described. An overall recovery of 25% with a purification of 106 has been achieved. Certain of the physical and chemical characteristics of XII have been elucidated. Selective chemical modification of functional groups and a variety of enzymatic assays have been employed in an effort to shed light on the mechanism of action of this procoagulant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1969
1969
1980
1980

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The average SD was found to be 0.71%. Also listed for comparison are the values previously published for the amino acid analysis of human HF by Speer, Ridgway, and Hill (47). We agree on the large number of charged residues present, but discrepancies in the amounts of several residues, most notably cysteine, were observed.…”
Section: Resultssupporting
confidence: 81%
“…The average SD was found to be 0.71%. Also listed for comparison are the values previously published for the amino acid analysis of human HF by Speer, Ridgway, and Hill (47). We agree on the large number of charged residues present, but discrepancies in the amounts of several residues, most notably cysteine, were observed.…”
Section: Resultssupporting
confidence: 81%
“…The studies presented in this paper were done with the aim of obtaining functionally pure factor XII a, contact activation product or factor Xla, and kinin-forming substances. Speer et al (45) reported to have obtained activated factor XII from human plasma by adsorption to and desorption from celite, followed by several preparative steps. The purified substance isolated by these investigators although migrating as a y-globulin, at pH 8.6, had an apparent isoelectric point of 5.2, eluted with increasing pH during cation-exchange chromatography and h ad an estimated molecular weight of about 20,000 by sedimentation equilibrium, but above 100,000 by gel filtration.…”
Section: Discussionmentioning
confidence: 99%
“…This was based on the method of Speer et al ( 45) modified as follows: The celite ("Hyflo", Super Ce!, Johns-Manville, Port Credit, Ontario) was suspended in 0.001 M Tris HCl (pH 8.0). The excess buffer was separated by centrifugation and the celite evenly suspended in the plasma (150 mg celite per ml plasma).…”
Section: P Reparation Of Celite Eluatesmentioning
confidence: 99%
“…Received for publication 2 September 1975 and in revised form 9 December 1975. plasma. Until recently, however, information concerning the molecular structure of the protein has been sparse and sometimes conflicting (2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, however, information concerning the molecular structure of the protein has been sparse and sometimes conflicting (2)(3)(4)(5)(6). The confusion has been undoubtedly due, in part, to the multiple forms of the enzymatically active Hageman factor moiety that result from differing purification and manipulatory techniques used by various investigators.…”
Section: Introductionmentioning
confidence: 99%